Leopoldo María Panero and Lois Pereiro: Poetics of Transgression - Piñeiro Pais, Laura (Madrygal. Revista de Estudios Gallegos, 2015)
In this article we will approach two types of poetry which are very similar: that of Leopoldo María Panero and that of the Galician writer Lois Pereiro, two figures that renewed the lyrical poetry of the last quarter of the 20th century. This study will not focus exclusively on the similarities among the two poetic styles, but it will also deal with the biography of both authors, closely related to their literary production.
Keywords: Leopoldo María Panero; Lois Pereiro; lyric; 20th century; biography.